Treatment of wastewater from the washing process of a municipal solid waste collection container by electrochemical treatment using different anode materials: a statistical optimization - Takatas, Betul; Erkan, Hanife Sari (SPRINGER HEIDELBERG, 2023)
An underground municipal solid waste (MSW) container should be washed periodically to prevent/reduce odor and leachate production. In this study, the treatment process of wastewater derived from the washing process of an MSW container was investigated using the electrochemical (EC) treatment process with different anode materials (Fe, TiO2, and graphite). Response surface methodology (RSM) was used to evaluate the effect of process parameters such as initial pH, applied current, and reaction time on chemical oxygen demand (COD), Tannin/Lignin, and color removals. According to the results obtained from the RSM models, all process parameters were significant. The optimum process parameters in terms of COD removal were derived from the models for each anode material. Under the optimized conditions, the COD removals were determined to be 93.25%, 75.95%, and 98.46% for Fe-Fe, TiO2-Fe, and graphite-Fe electrode pairs, respectively. The color and Tannin/Lignin removals were determined as 98.12% and 77.78% for the Fe-Fe, 92.76% and 98.45% for the TiO2-Fe and 94.50% and 79.56% for the graphite-Fe electrode pair, respectively. The specific energy consumption (SEC) values were found as 46.95, 300.02, and 32.95 kWh/m(3) for each electrode combination given above, respectively. In terms of both removal efficiencies and SEC, the most effective anode material was determined as graphite, followed by iron.
Keywords: Municipal solid waste; Washing wastewater; MSW container; Wastewater treatment; Electrocoagulation; Electrooxidation; ELECTROCOAGULATION-ELECTROOXIDATION PROCESS; EFFLUENT OPTIMIZATION; ORGANIC POLLUTANTS; LANDFILL LEACHATE; OXIDATION; WASTEWATERS; REMOVAL; DEGRADATION; PH; FUNDAMENTALS; Environmental Sciences & Ecology